Transformation ratio at wakefield excitation by linearly shaped sequence of short relativistic electron bunches in plasma - Levchuk, I.P.; Maslov, V.I.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2015)
Wakefield excitation by long sequence of short Gaussian bunches of relativistic electrons and electron bunch acceleration in excited wakefield is numerically simulated for the parameters of the experiments. It is shown that at change of the system parameters and shaping laws of sequence of bunches of relativistic electrons in the intervals of finite width the transformation ratio remains large.